A Review on Constant Switching Frequency Techniques for Direct Torque Control of Induction Motor - Auzani Jidin; Kasrul Abdul Karim; Khairi Rahim; Logan Raj Lourdes Victor Raj; Sundram Ramahlingam; Tole Sutikno (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The Direct Torque Control (DTC) of induction machine has received wide acceptance in many Variable Speed Drive (VSD) applications due to its simple control structure and excellent torque dynamic control performances. However, the conventional DTC which employs a two-level inverter and hysteresis controllers produces two major drawbacks, namely, larger torque ripple and variable switching frequency, which might produce a very high switching frequency (or power loss), particularly at a very low speed operation. This paper highlight the common methods used to provide the constant switching frequency for DTC drives for Induction Motor that able to minimize the power losses and reduced the torque ripple.